2008
DOI: 10.1590/s0103-50532008000800010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of lipid compounds in sediments from Conceição Lagoon, Santa Catarina Island, Brazil

Abstract: Compostos orgânicos provenientes de cinco amostras de sedimentos e um perfil com 75 cm foram coletados na Lagoa da Conceição, localizada na Ilha de Santa Catarina, com o objetivo de avaliar fontes de matéria orgânica. Os resultados que foram baseados na relação C:N:P, abundância relativa dos esteróis (com predomínio dos C 27 ), álcoois (0,2-1,2 µg g -1 ) e hidrocarbonetos lineares (0,4-5,0 µg g -1 ), e no uso do Índice Preferencial de Carbono (CPI), indicaram que a matéria orgânica é preferencialmente de orige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Only one location (Bab5) in the Babitonga Bay showed a concentration of OP (251.6 μg g −1 ) much higher than the IP concentration (212.7 μg g −1 ). Previous studies have indicated that the proportion of OP to IP seems to be affected by sources of phosphorus and shown that IP is usually accountable for 60% of the TP in sediments without anthropogenic input (Mater et al 2004;Silva et al 2008). …”
Section: Granulometry and Bulk Geochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one location (Bab5) in the Babitonga Bay showed a concentration of OP (251.6 μg g −1 ) much higher than the IP concentration (212.7 μg g −1 ). Previous studies have indicated that the proportion of OP to IP seems to be affected by sources of phosphorus and shown that IP is usually accountable for 60% of the TP in sediments without anthropogenic input (Mater et al 2004;Silva et al 2008). …”
Section: Granulometry and Bulk Geochemical Parametersmentioning
confidence: 99%
“…Studies on the environmental aspects of harbors are important since these environments are recipients of toxic chemical inputs from a wide variety of pollution sources and they can affect marine coastal ecosystems through sediment dredging, seawater diffusion, or advective sediment transport. There are few published studies on the characterization of organic extracts from sediments along the Santa Catarina coast (Mahiques et al 1999;Mater et al 2004;Alexandre et al 2006;Silva et al 2008). At the molecular level, little is known about the types of hydrocarbons or other compounds that may be found in the sediments of Babitonga Bay, the Itajaí-Açu River mouth, and Imbituba Harbor.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Concentrations and indices regarding AH and NA in our samples are summarized in Table 2. The AH concentrations varied from 12.6 to 2,267.4 µg g -1 of sediment dry weight (dw) and from 38.5 to 34,883.1 µg g -1 of organic carbon weight (OC), whereas NA concentrations ranged from 0.9 to 45.6 µg g -1 dw and from 55.1 to 7,013.5 µg g -1 OC.…”
Section: Aliphatic Hydrocarbons and N-alkanesmentioning
confidence: 99%
“…Biomarker analysis of soluble organic matter in the coals has contributed to our understanding of the paleoenvironment of the mires (Waples and Machihara, 1991;Silva et al, 2008). In gas chromatograms of the studied samples, n-alkanes are found in the range of C 22 -C 32 , indicating a lagoonal and/or terrestrial environment (Filley et al, 2001;Riboulleau et al, 2007;Silva et al, 2008).…”
Section: Peakmentioning
confidence: 98%
“…In gas chromatograms of the studied samples, n-alkanes are found in the range of C 22 -C 32 , indicating a lagoonal and/or terrestrial environment (Filley et al, 2001;Riboulleau et al, 2007;Silva et al, 2008). 17α (H) -homohopane ratios are essential as a paleoclimate indicator (Waples and Machihara, 1991).…”
Section: Peakmentioning
confidence: 99%